2008
DOI: 10.1093/bja/aen202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prophylactic 5-HT3 receptor antagonists on pruritus induced by neuraxial opioids: a quantitative systematic review

Abstract: Pruritus is a frequent adverse event observed after neuraxial administration of opioids. Central 5-hydroxytryptamine subtype 3 (5-HT3) receptors may be activated in this process. This systematic review aimed to evaluate the efficacy of prophylactic 5-HT3 receptor antagonists on neuraxial opioid-induced pruritus. We searched Medline, Embase, and Cochrane Collaboration Library databases. Studies were evaluated with the Oxford Validity Scale. Studies with a score of 3 or more and reporting prophylactic administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
72
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 46 publications
1
72
1
1
Order By: Relevance
“…In a systematic review and meta-analysis, George et al 35 found that prophylactic 5-HT3 receptor antagonists reduced the severity of pruritus and the need for rescue medication among parturients receiving spinal morphine for cesarean delivery. Likewise, Bonnet et al 19 found that prophylactic 5-HT3 receptor antagonists (including ondansetron, tropisetron, granisetron, and dolasetron) lead to decreased need for pruritus rescue medication after spinal opioid (morphine, sufentanil, or fentanyl). Our analysis also suggests a reduced need for rescue treatment in patients receiving intrathecal fentanyl or sufentanil, especially in nonobstetric patients and when the treatment is initiated before spinal opiate administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic review and meta-analysis, George et al 35 found that prophylactic 5-HT3 receptor antagonists reduced the severity of pruritus and the need for rescue medication among parturients receiving spinal morphine for cesarean delivery. Likewise, Bonnet et al 19 found that prophylactic 5-HT3 receptor antagonists (including ondansetron, tropisetron, granisetron, and dolasetron) lead to decreased need for pruritus rescue medication after spinal opioid (morphine, sufentanil, or fentanyl). Our analysis also suggests a reduced need for rescue treatment in patients receiving intrathecal fentanyl or sufentanil, especially in nonobstetric patients and when the treatment is initiated before spinal opiate administration.…”
Section: Discussionmentioning
confidence: 99%
“…Although a meta-analysis by Bonnet et al,19 in 2008, failed to demonstrate an effect of 5-HT3 receptor antagonists on intrathecal opioid-induced pruritus, the study primarily focused on intrathecal morphine and pooled studies of different 5-HT3 receptor antagonists at different doses. To date, the results of single-center trials evaluating prophylactic 5-HT3 receptor antagonists for intrathecal opioid-mediated pruritus have been mixed.…”
mentioning
confidence: 99%
“…There were two earlier systematic reviews 34,35 on the pharmacological intervention of opioid-induced pruritus, but both did not focus on butorphanol and studies of pediatric patients were excluded. In our systematic review, four trials in children were available, and the combined data from three trials reporting the occurrence of pruritus showed that butorphanol could significantly reduce morphine-induced pruritus.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review by Bonnet et al published after completion of our trial concluded that 5-HT3 receptor antagonists may be effective in preventing neuraxial opioid-induced pruritus, but that more trials were needed to confirm this finding as there seemed to be a publication bias in the current literature. 13 The inclusion of a placebo group would have addressed this issue. Another possible confounding factor in our study was the routine administration of diclofenac to all patients, as non steroidal anti-inflammatory drugs may be effective in reducing pruritus.…”
Section: Discussionmentioning
confidence: 99%